Frequency, Pattern of Injuries and Weapon used in Medico Legal Cases (Medical Forum Monthly, 2024)
Objective: To study the frequency, Pattern of Injuries and weapon used in Medico legal cases.Design of Study: Retrospective observational study.Place and Duration of Study: This study was conducted at the Sardar Begum Teaching Hospital Sialkot, and forensic department Khyber Medical College, Peshawar from January 2015 to December 2016.Materials and Methods: Two thousand and fifteen cases were included in the study. The Performa was designed to record age, sex, socio economic status, area of the victim, type of injury, number of injuries and weapon used. The fully informed consent of every patient was recorded before examination. The permission of ethical committee of the institute was also taken. The data was analyzed by SPSS version 10. Results: There were maximum (64.2%) n=1413 medico legal cases at age 21-30 years, (59.8%) n=1317 male and (4.4%) n=96 female. Minimum medico legal cases (0.7%) n= 17 at the age of 61-70 years, (0.6%) n= 14 male and (0.1%) n=3 female as shown in table no. 1. It was seen that maximum (77.3%) n= 1704 from urban area (72.9%) n= 1607 male and (4.4%) n= 97 female medico legal and medico legal cases rural area were (22.6%) n= 498, (19.6%) n=432 male and (3.0%) n=163 female as shown in table no.2. Medico legal cases of firearm were at the top (68.8%) n= 1517, (65.84%) n= 1450 male and (3.04%) n= 67 female in the society but punctured wound medico legal cases were minimum (0.3%) n= 07, (0.22%) n= 05 male and (0.09%) n=2 female in the society as shown in table no. 3. The weapon used in medico legal cases was firearm at the top (68.8%) n=1517 and pointed end weapon was used minimally (0.3%) n=07 as shown in table no .4. There were (75%) n=1651 cases of homicide, (0.6%) n= 15 cases of suicide and (24.4%) n= 536 cases of accident in the study as shown in table no.5. Conclusion: The study showed that (75%) cases were of homicidal in nature, (0.6%) cases of suicidal nature and (24.4%) cases of accidental in nature.